Analisis Hubungan Grit dan Psychological Well-Being pada Siswa Madrasah Aliyah dengan Sistem Boarding School - Nadia Ama Natuz Zahro; Ari Khusumadewi (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aimed to empirically examine the relationship between grit and psychological well-being among Islamic boarding school students. Students living in boarding school environments face various personal, social, and academic demands that may relate to their psychological well-being, which plays an important role in supporting academic functioning, mental health, and personal development. Methods – A quantitative approach was employed using a cross-sectional explanatory survey design. The sample comprised all 105 grade XI students at Ma'had Darul Ilmi MAN 2 Kota Kediri, selected through total sampling. Data was gathered via a questionnaire consisting of the Short Grit Scale and a psychological well-being scale and subsequently analyzed using simple regression analysis. Findings – The results revealed a significant relationship between grit and psychological well-being (F = 21.300; p < 0.05). Interestingly, the relationship was negative (B = -0.505; t = -4.615), indicating that higher levels of grit were associated with lower psychological well-being among students. This finding may relate to contextual characteristics of the boarding school environment and the specific population studied. Furthermore, grit explained 17.1% of the variance in psychological well-being, while the remaining 82.9% may be associated with other factors beyond the scope of this study.Research Implications – The findings highlight that psychological well-being among boarding school students may be associated with multiple psychological and contextual factors. Further research is recommended to explore additional variables that may relate to students’ psychological well-being in boarding school settings.